Breaking the Ice to Build Relationships: Using Icebreakers to Create New Relationships, Promote Emotional Safety, and Incorporate Social and Emotional Learning: Editor: Ferman Konukman. Issue 5 (12th June 2020) - Dressel, Dennis Patrick
Abstract : The physical education classroom is a unique opportunity for students to participate in a variety of experiences that a normal classroom would not be able to provide. These experiences build attributes that students can use for the rest of their lives. Some of the attributes that students are exposed to include character, teamwork, trust, respect for themselves and others, goal setting, and building and maintaining relationships. Relationship building in particular is a very important skill that is used every day throughout our students' lives. Whether it be relationships with peers, parents, teachers, or other school staff, students need to learn these life skills now in order to use them later in life with their bosses, coworkers, and significant others.